New brand identity for apricot seed product, in order to gain consumer trust / Azrul Izwan Ibrahim - Ibrahim, Azrul Izwan (Faculty of Art and Design, 2013)
Cancer is a chronic disease and could lead to fatality. The main reason why the researcher highlighted apricot seed product because the researcher would like to share to public other alternative medication in treating cancer, in which it is believe more effective than conventional method. To make it to be known by other, the advertisement and rebranding is a method to deliver the information and to get trust from public about this product. The purpose of this study is to highlight the traditional medicine to the public by rebranding the identity.To tell the goodness in medical usage, and how can be implementedin daily routine. All kind of traditional medicine has their own benefit and goodness depends on how is the way they are being consumed. The objective and research methodology on how the effective of this product which is Apricot seed is one of new option to prevent cancer. The main purpose is to collect all data about cancer especially from Malaysian indirectly can approve the result of the research. The research data collection is getting through questionnaire and many references. The questionnaire prepared to survey how is the awareness among public about cancer and apricot seed as alternative treatment. Out of 47 respondents, 17 respondents claimed have been cured by apricot seed while the rest from public. All respondent were 47 people around Malysia that were contribute in this servey. The conclussion is on how will propose and we contribute this product to the entire of Malysia especially. The recommendation, in Malaysia not many people know about the goodness of apricot seed, the involvement of government and pharmacy agency to popularise is a beginning step to make it a realisation, so this product can be produced and marketed throughout the country.